The Relationship Between Appreciation and the Attitude of Local Peoples Towards Foreign Workers - Yahya, Mohamad Shyafiq Ezzat bin; Idris, Sidah; Sinun, Wajiran (Malaysian Journal of Business and Economics (MJBE), 2019)
As an effect of globalization, it was easier to see foreigners everywhere furthermore with the help of the advancement of technology of information and transportation. This was especially true nowadays as we can see the trends of increase in foreign workers. Usually, these foreign workers are subject to bad impression from the locals especially in the case of an increase in crimes rate, job opportunity and wage differences. Even though the foreign workers are usually subjected to bad impression, we cannot deny that they also bring benefits to the country’s economy and some locals did appreciate it. This paper aims to identify the relationship between appreciation and the attitude of locals towards foreign workers. This study will employ secondary data in order to identify the relationship between them. It was expected that, from the finding, we can conclude that appreciation will have a positive relationship towards the attitude of locals towards foreign workers. The result is expected to indicate whether appreciation is related to the attitude towards foreign workers or not. This paper will contribute to future research and the body of knowledge.